Morbidity and mortality of bone metastases in advanced adrenocortical carcinoma: a multicenter retrospective study. Issue 5 (May 2019) - Berruti, Alfredo; Libè, Rossella; Laganà, Marta; Ettaieb, Hester; Sukkari, Mohamad Anas; Bertherat, Jérôme; Feelders, Richard A; Grisanti, Salvatore; Cartry, Jérôme; Mazziotti, Gherardo; Sigala, Sandra; Baudin, Eric; et al.
Abstract : Introduction: Adrenocortical carcinoma (ACC) is a rare cancer that commonly spreads to the liver, lungs and lymph nodes. Bone metastases are infrequent. Objective: The aim of this report was to describe the clinical characteristics, survival perspective, prognostic factors and frequency of adverse skeletal-related events (SREs) in patients with ACC who developed bone metastasis. Methods: This is a retrospective, observational, multicenter, multinational study of patients diagnosed with bone metastases from ACC who were treated and followed up in three European countries (France, Italy and The Netherlands) and one center in the United States. Results: Data of 156 patients were captured. The median overall survival was 11 months. SREs occurred in 47% of patients: 17% bone fractures, 17% spinal cord compression, 1% hypercalcemia, 12% developed more than one SRE. In multivariate analysis, cortisol hypersecretion was the only prognostic factor significantly associated with a higher mortality risk (hazard ratio (HR) 2.24, 95% confidence interval (CI): 1.19–4.23, P = 0.013) and with the development of a SREs (of border line significance). The administration of antiresorptive therapies (bisphosphonates and denosumab) was associated with a lower risk of death, even if not significant, and their survival benefit appeared confined in patients attaining serum mitotane levels within the therapeutic range. Conclusion: Bone metastases in ACC patients are associated with poor prognosis and high risk of SREs. Cortisol hypersecretion was the only prognostic factor suggesting a potential benefit from antisecretory medications. The therapeutic role of bisphosphonates and denosumab to improve patient outcome deserves to be tested in a prospective clinical trial.